The principle of fair play in the aspect of compliance with rules and regulations in the opinion of junior high schools students in Lodz - Kowalska, Jolanta Elżbieta (Journal of Education, Health and Sport, 2019)
The idea of fair play can act an important role in the education process, especially among students of adolescence (middle school) age. Therefore it was important to undertake such educational activities (implementation of an educational project), so the youth could understand exactly what is the principle of fair play, not only in life but also in all other aspects. After the implementation of the educational project „I am fair” dedicated to lower class of secondary schools’ pupils in Łódź (14-15 y.o.), it was decided to evaluate, if and to what extent, students who took part in the project, had changed their awareness and declared behaviour of fair play, in the aspect of compliance with rules and regulations in both sport and life. Methodology: The study was conducted by diagnostic survey using a situational test "Fair play in sport and life". The results were analysed taking into account the change in the responses of students, who completed the questionnaire twice: before (pre- test) and after (post- test) the implementation of the project. There were taken into account all respondents (N= 1387) and variables - the declaration of supporting or not the football and the gender. The study was conducted by two waves- in September 2011 (pre- test) and June 2012 (post- test). Results: Results of post- test survey proved the improvement of declared behaviour among all tested groups. CONCLUSIONS On the one hand, sport contributes to the escalation of unwanted behaviours, on the other hand it becomes an educational tool. Education supported by fair play values brings expected effects and demanded changes, both in sport and in life.